2013
DOI: 10.1111/j.1365-2230.2012.04478.x
|View full text |Cite
|
Sign up to set email alerts
|

Coexistence of marginal zone cutaneous B-cell lymphoma and classic Hodgkin disease: does a biological relationship exist?

Abstract: The coexistence of non-Hodgkin lymphoma (NHL) and Hodgkin disease (HD) in the same patient, although previously reported, is very unusual. This situation is extremely rare when the first diagnosis is a cutaneous B NHL, and exceptional if there is no personal background of cytostatic treatment. We report a 44-year-old man who developed cutaneous nodules over a period of two years. A marginal zone cutaneous B-cell lymphoma was diagnosed. On staging investigation a mass in the lingual tonsil was found and excisio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 10 publications
(24 reference statements)
0
5
0
Order By: Relevance
“…There were no clinical trials identified that outlined any specific staging or response assessment criteria for WR. The entire systematic review described 166 unique cases of WR involvement in patients with HL (Table S1) 7‐30,32,37‐49 . Seven pediatric cases were identified, of which six were male patients 12,13,31,38,42,44,46 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…There were no clinical trials identified that outlined any specific staging or response assessment criteria for WR. The entire systematic review described 166 unique cases of WR involvement in patients with HL (Table S1) 7‐30,32,37‐49 . Seven pediatric cases were identified, of which six were male patients 12,13,31,38,42,44,46 .…”
Section: Resultsmentioning
confidence: 99%
“…Seven pediatric cases were identified, of which six were male patients 12,13,31,38,42,44,46 . Although stage was not specified for all of the pediatric cases, at least two cases were isolated to WR alone, 13,31 and several cases in adults were isolated to WR 7,18,21,24,28,39,40,41,43,45,49 . Common clinical presentations for WR involvement included nasal obstruction or congestion, hoarseness, and painless tonsillar swelling.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…One of our patients was diagnosed with Hodgkin lymphoma 8 years after the diagnosis of PCMZL. An association of PCMZL with Hodgkin lymphoma has rarely been reported …”
Section: Discussionmentioning
confidence: 99%
“…Cutaneous lymphomas represent a unique group of lymphomas and are the second most frequent extranodal lymphomas. 1,2 Cutaneous lymphomas are identified by lymphoproliferative skin infiltrates of T-cell, B-cell, or natural killer cell lineage, and seen confined to the skin with paucity of extracutaneous manifestations.…”
Section: Discussionmentioning
confidence: 99%